The Technical readiness for Applying Modern Syllabus of Science at the Secondary Stage in Taif Governorate - Al-Nafie, Abdullah Jaza Fayhan (Journal of Educational and Psychological Sciences, 2025)
The current study aimed to determine the level of secondary science teachers’ technological readiness for using modern curricula, identify the extent of readiness in terms of material resources and necessary equipment, and specify the challenges that limit effective technology integration in modern science curriculum implementation.The study employed the descriptive-analytical approach. The sample consisted of (144) secondary science teachers in Taif city, who were selected using a simple random sampling method. A questionnaire was used as the primary research tool, and data analysis was conducted using the Statistical Package for the Social Sciences (SPSS).The results indicated that secondary science teachers in Taif generally reported a high degree of technological readiness to implement modern science curricula, with a mean score of (3.62). However, the readiness concerning material resources and equipment was rated as moderate (Mean = 3.60). Furthermore, the study identified moderate challenges hindering technology utilization (Mean = 3.50) faced by the teachers. Based on these findings, the researcher put forth several key recommendations, including: enhancing the teachers’ awareness of the critical importance of integrating technology into the educational process; urging relevant authorities to provide the necessary material resources and equipment to Taif high schools; and encouraging the Taif Secondary Education Administration to address technology integration obstacles, particularly those related to heavy teaching loads and large student numbers per classroom.